Avian influenza in Colombia: A One Health perspective on surveillance, intervention, and policy integration - Ciuoderis, Karl A (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Avian influenza remains a significant global health issue, threatening animal and human populations. The natural reservoirs of influenza A viruses (IAVs) are wild birds, and their transmission dynamics can influence disease outbreaks in domestic poultry and humans. Colombia, due to its geographic location and diverse ecosystems, faces unique challenges in the surveillance and control of avian influenza. Objective: This work aims to provide a comprehensive overview of avian influenza in Colombia from a One Health perspective, highlighting surveillance, intervention strategies, and policy integration to mitigate disease spread. Methods: A literature review was conducted to consolidate data on avian influenza cases in Colombia, including reports of outbreaks in poultry and wild birds. Risk factors, transmission routes, and prevention strategies were analyzed, emphasizing the role of migratory birds and ecological influences. Results: Colombia has experienced highly pathogenic avian influenza (HPAI) outbreaks, primarily affecting backyard poultry and wild birds. The review identifies key risk areas influenced by migratory bird pathways, poultry farming practices, and biosecurity measures. Effective surveillance systems and rapid response protocols are essential to prevent further spread. Conclusions: Adopting a One Health approach that integrates veterinary, public health, and environmental efforts is critical to mitigating avian influenza in Colombia. Strengthening surveillance, improving vaccination strategies, and enhancing biosecurity measures can reduce transmission risks. International cooperation is also necessary to monitor migratory bird movements and implement preventive measures against potential outbreaks.